(untitled) - Mursell, Gordon; (1949-...) (Great Britian, 2001)
This wide-ranging historical survey provides an indispensable resource for those interested in exploring, teaching, or studying English spirituality. In two stand-alone volumes, it traces history from Roman times until the year 2000. The main Christian traditions and a vast range of writers and spiritual themes, from Anglo-Saxon poems to late-modern feminist spirituality, are included. These volumes present the astonishing richness and variety of responses made by English Christians to the call of the divine during the past two thousand years.
Keywords: Church history